2022
DOI: 10.3390/foods11162478
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gaseous Citral on Table Grapes Contaminated by Rhizopus oryzae ITEM 18876

Abstract: Rhizopus oryzae is responsible for rapidly producing a deliquescent appearance in grape berries, generally favoured by cold chain interruptions. To counteract fruit spoilage and to meet consumer acceptance, innovative strategies based on the application of natural compounds are ongoing. Due to their biological activities, including antimicrobial ones, natural flavour compounds extend the shelf life and improve the nutritional value as well as the organoleptic properties of foods. Thus, in this work, the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Free citral showed a MIC value of 0.8 mg mL −1 against B. cereus and 2 mg mL −1 against E. coli and S. aureus [ 68 ]. However, the main application of citral is its use as an antifungal agent, as demonstrated against different fungal strains [ 69 , 70 , 71 ]. As regards cinnamaldehyde, it showed higher antibacterial activity than cinnamon oil against Gram-positive bacteria [ 72 ].…”
Section: Classification and Antimicrobial Activity Of Plant Antimicro...mentioning
confidence: 99%
“…Free citral showed a MIC value of 0.8 mg mL −1 against B. cereus and 2 mg mL −1 against E. coli and S. aureus [ 68 ]. However, the main application of citral is its use as an antifungal agent, as demonstrated against different fungal strains [ 69 , 70 , 71 ]. As regards cinnamaldehyde, it showed higher antibacterial activity than cinnamon oil against Gram-positive bacteria [ 72 ].…”
Section: Classification and Antimicrobial Activity Of Plant Antimicro...mentioning
confidence: 99%
“…In recent years, bamboo anti-mildew research has become a hot spot in which natural antimicrobial agent-related research has gradually gained attention. One of the natural antimicrobial agents is citral, which is primarily derived from the essential oil of the Chinese medicine Cyperus rotundus, which has the advantages of a broad spectrum of bacterial inhibition and being environmentally friendly and will have a greater outlook for applications in the anti-mildew of bamboo [ 9 , 10 , 11 , 12 , 13 ]. Currently, the study on the inhibition performance of citral against common bamboo molds carried out by the authors’ team [ 14 , 15 ] found that the inhibition rate of bamboo molds exceeded 100% when the concentration of citral was 75 mg mL −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Quintieri et al [10] investigated the effectiveness of citral, a flavour component found in plant and fruit essential oils, against Rhizopus oryzae ITEM 18876. In vitro tests showed that citral was effective against this spoilage microorganism at concentrations equal to the minimal inhibitory concentration (MIC) and 4-fold MIC.…”
mentioning
confidence: 99%